Interdisciplinary Treatment to Arc Welding Power Sources - Vendan, S. Arungalai; Gao, Liang; Garg, Akhil; Kavitha, P.; Dhivyasri, G.; SG, Rahul; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents the fundamentals of arc phenomena, various arc welding power sources, their control strategies, welding data acquisition, and welding optimization. In addition, it discusses a broad range of electrical concepts in welding, including power source characteristics, associated parameters, arc welding power source classification, control strategies, data acquisitions techniques, as well as optimization methods. It also offers advice on how to minimize the flaws and improve the efficacy and performance of welds, as well as insights into the mechanical behavior expressed in terms of electromagnetic phenomena, which is rarely addressed. The book provides a comprehensive review of interdisciplinary concepts, offering researchers a wide selection of strategies, parameters, and sequences of operations to choose from.
Introduction -- Evolution of Power Source and Critical Terminologies -- Classification of Arc Welding Power Sources -- Arc Welding Control System -- Power Source Applications and Challenges -- Sensors in Welding Data Acquisition -- Optimization Techniques of Welding Parameters -- References -- Conclusions -- Appendix.
Keywords: Manufactures; Electric power production; Metals; Control engineering; Machines, Tools, Processes; Electrical Power Engineering; Metals and Alloys; Control and Systems Theory